Communities of practice and translation: An introduction - Patrick Cadwell; Federico M. Federici; Sharon O'Brien (JoSTrans: The Journal of Specialised Translation)
A community of practice is a concept that can be used to examine how groups of people share knowledge and learn. Researchers in Translation and Interpreting Studies have found value in the concept to study translator and interpreter education and to research knowledge sharing and collaboration among networks of professional translators, fansubbers, translation activists, and public service interpreters and translators. Many of these previous studies examined how translators and interpreters (or those who saw themselves as translators and interpreters) learned by doing and formed communities around a shared practice. Our motivation for this special issue was to explore settings in which individuals who might not identify themselves as translators or interpreters share knowledge about translation or interpreting. We use this introductory article to expand on this motivation, outline fundamental ideas related to communities of practice, summarise each contribution to the issue, and suggest themes and future directions that can be derived from the research presented.